2022
DOI: 10.20517/mrr.2021.07
|View full text |Cite
|
Sign up to set email alerts
|

A breath of fresh air in microbiome science: shallow shotgun metagenomics for a reliable disentangling of microbial ecosystems

Abstract: Next-generation sequencing technologies allow accomplishing massive DNA sequencing, uncovering the microbial composition of many different ecological niches. However, the various strategies developed to profile microbiomes make it challenging to retrieve a reliable classification that is able to compare metagenomic data of different studies. Many limitations have been overcome thanks to shotgun sequencing, allowing a reliable taxonomic classification of microbial communities at the species level. Since numerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Previous metagenome studies have reported 97–99 % accuracy for pathogen identification at genus level for microbes using shallow sequencing (<500 000 sequences) [41–44]. Results from our study broadly agreed with those of previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Previous metagenome studies have reported 97–99 % accuracy for pathogen identification at genus level for microbes using shallow sequencing (<500 000 sequences) [41–44]. Results from our study broadly agreed with those of previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…We using more advanced techniques, i.e. third-generation sequencing technologies (shallow) metagenomics [96,97] for more accurate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting genome sequence has been polished through Polypolish (Wick and Holt, 2022 ) using Illumina paired-end reads. The whole process was managed by the MEGAnnotator2 pipeline (Lugli and Ventura, 2022 ).…”
Section: Methodsmentioning
confidence: 99%